2020
DOI: 10.2147/ijn.s269214
|View full text |Cite
|
Sign up to set email alerts
|

<p>Synergetic Influence of Bismuth Oxide Nanoparticles, Cisplatin and Baicalein-Rich Fraction on Reactive Oxygen Species Generation and Radiosensitization Effects for Clinical Radiotherapy Beams</p>

Abstract: This study aimed to quantify synergetic effects induced by bismuth oxide nanoparticles (BiONPs), cisplatin (Cis) and baicalein-rich fraction (BRF) natural-based agent on the reactive oxygen species (ROS) generation and radiosensitization effects under irradiation of clinical radiotherapy beams of photon, electron and HDR-brachytherapy. The combined therapeutic responses of each compound and clinical radiotherapy beam were evaluated on breast cancer and normal fibroblast cell line. Methods: In this study, indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 112 publications
2
6
0
Order By: Relevance
“…The presence of radiosensitizers in the cancer cells could increase ROS generation. 33 These effects may be related to apoptosis induction, which was observed in this study. Indeed, balance among apoptosis induction and its inhibition has a critical role in homeostasis of various tissues.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The presence of radiosensitizers in the cancer cells could increase ROS generation. 33 These effects may be related to apoptosis induction, which was observed in this study. Indeed, balance among apoptosis induction and its inhibition has a critical role in homeostasis of various tissues.…”
Section: Resultssupporting
confidence: 59%
“…The presence of radiosensitizers in the cancer cells could increase ROS generation. 33 These effects may be related to apoptosis induction, which was observed in this study.…”
Section: Resultssupporting
confidence: 59%
“…Furthermore, Sisin et al. [17], reported that bismuth oxide nanoparticles (BumPs), cisplatin (Cis), and baicalein‐rich fraction (BRF) have the synergistic effect. They also illustrated the effects of natural‐based agent on ROS under irradiation by photon, electron and high dose rate (HDR) brachytherapy of clinical radiotherapy beams on breast cancer and normal fibroblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…Day by day, cancer is becoming more severe as well as a common disease all over the world; 2 million women were affected by breast cancer in the year 2018; similarly, prostate, colorectal, stomach, and lung cancer cases are also drastically increasing. Breast cancer causes leading counts of death among females in over 103 countries [4]. Generally, constipation, dizziness, dermatitis, dry mouth, nausea, headache, insomnia diarrhea, and drowsiness are the common problems by the time of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin and BiONPs are possible radiosensitizers that might increase the efficacy of radiation in eradicating cancer cells. When used in radiotherapy, this combination of such powerful radiosensitizers may have numerous implications [4]. It was demonstrated that BiONPs, cisplatin, and combined brachytherapy had a synergetic effect that will benefit future chemoradiotherapy approaches in cancer medicine [49].…”
mentioning
confidence: 99%